Recent Advances in Electrochemical Glycobiosensing - Germarie Sánchez-Pomales; Rebecca A. Zangmeister (International Journal of Electrochemistry)
Biosensors based on electrochemical transduction mechanisms have recently made advances into the field of glycan analysis. These glyco-biosensors offer simple, rapid, sensitive, and economical approaches to the measurement need for rapid glycan analysis for biomarker detection, cancer and disease diagnostics, and bioprocess monitoring of therapeutic glycoproteins. Although the prevalent methods of glycan analysis (high-performance liquid chromatography, mass spectrometry, and nuclear magnetic resonance spectroscopy) provide detailed identification and structural analysis of glycan species, there are significantly few low-cost, rapid glycan assays available for diagnostic and screening applications. Here we review instances in which glyco-biosensors have been used for glycan analysis using a variety of electrochemical transduction mechanisms (e.g., amperometric, potentiometric, impedimetric, and voltammetric), selective binding agents (e.g., lectins and antibodies), and redox species (e.g., enzyme substrates, inorganic, and nanomaterial).